2015
DOI: 10.1016/j.etap.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olfactory manganese exposure on anxiety-related behavior in a mouse model of iron overload hemochromatosis

Abstract: Manganese in excess promotes unstable emotional behavior. Our previous study showed that olfactory manganese uptake into the brain is altered in Hfe−/− mice, a model of iron overload hemochromatosis, suggesting that Hfe deficiency could modify the neurotoxicity of airborne manganese. We determined anxiety-related behavior and monoaminergic protein expression after repeated intranasal instillation of MnCl2 to Hfe−/− mice. Compared with manganese-instilled wild-type mice, Hfe−/− mice showed decreased manganese a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…In addition, the hematocrit and total iron levels in lungs, liver, and blood also showed no significant change (Tables 2, 3). Similar results were observed in mice after intranasal instillation of Mn for 3 weeks (Ye et al, 2015a); iron status in the liver and brain were unaltered upon Mn instillation. However, Mn exposure by drinking water for 5 weeks significantly decreased iron levels in the liver (Alsulimani et al, 2015).…”
Section: Figsupporting
confidence: 83%
“…In addition, the hematocrit and total iron levels in lungs, liver, and blood also showed no significant change (Tables 2, 3). Similar results were observed in mice after intranasal instillation of Mn for 3 weeks (Ye et al, 2015a); iron status in the liver and brain were unaltered upon Mn instillation. However, Mn exposure by drinking water for 5 weeks significantly decreased iron levels in the liver (Alsulimani et al, 2015).…”
Section: Figsupporting
confidence: 83%
“…The striatum was chosen for several reasons. Firstly, Mn levels were consistently lower in H67D mice among all Mn doses, suggesting a pronounced effect of H67D on Mn transport (Figure 2); secondly, the striatum is a brain region sensitive to Mn neurotoxicity 43 ; thirdly, the striatum showed significant neurochemical changes in response to both HFE deficiency and intranasal Mn exposure 30 . Neither Mn instillation nor H67D mutation affected the expression of DMT regardless of the existence of IRE.…”
Section: Resultsmentioning
confidence: 98%
“…These results indicate that loss of HFE function could enhance absorption as well as clearance of Mn. In addition, we found that HFE-knockout mice are resistant to memory deficits and emotional dysfunction induced by chronic intranasal Mn instillation compared with Mn-treated wild-type mice, suggesting that HFE deficiency could modify Mn-associated neurobehavioral problems 30, 31 . However, it is yet to be determined whether H67D mutation, a prevalent mutation in HH patients, alters Mn deposition in the brain and consequently modifies neurotoxicity after acute olfactory exposure.…”
Section: Introductionmentioning
confidence: 85%
“…Supporting this observation, Hfe-deficient mice that display iron overload increase brain Mn uptake after intranasal administration of Mn radioisotope [102]. This increase in Mn uptake from the olfactory route under Hfe deficiency altered the neurotoxicity of Mn post intranasal exposure [185].…”
Section: Olfactory Uptakementioning
confidence: 73%
“…Consistent to this observation, Rosemarie et al found an association between anxiety and environmental Mn exposure [256]. In contrast, Ye et al found intranasal exposure to MnCl2 reduced the anxiety [185]. This difference in anxiety response to Mn exposure in both studies could be due to different route of administration.…”
Section: Discussionmentioning
confidence: 85%